REPRESENTASI BUDAYA PATRIARKI PADA FILM NGERI-NGERI SEDAP (KAJIAN SEMIOTIKA ROLAND BARTHES - Nanda Ivena (2023)
The presence of film in real output in the category of mass communication exists as an alternative in entertainment media which has its own agenda to convey messages and information to the public. In contrast to other results of mass communication, film has a distinctive feature as a propaganda tool with an ideology in it. Like the film Ngeri-Ngeri Sedap which successfully shows the Batak tribe with patriarchal ideology in its meaning. The film Ngeri-Ngeri Sedap is directed by Bene Dion Rajagukguk which was released on June 2, 2022 and can be enjoyed to this day via the Netflix with a film background that tells the story of Batak culture. The film Ngeri-Ngeri Sedap managed to get many awards both at home and abroad. This study aims to reveal the meaning of patriarchal culture in the film Ngeri-Ngeri Sedap through a study of the meaning of signs, denotations, connotations, and myths through Roland Barthes' Semiotics and discusses the social reality of Batak culture and its relevance to reality in film. The method used in this study is descriptive qualitative using primary data sources, namely the Ngeri-Ngeri Sedap films and secondary data through literacy and interviews with expert sources. The researcher uses a scene per scene analysis unit in the discussion analysis. The final results of this study indicate the presence of patriarchal culture in the film Ngeri-Ngeri Sedap in its representation of the structuring of Batak culture, the reality of the film shown with the reality of patriarchal culture in the Batak tribe produces similarities with changes and dramatization according to the characteristics of a film. This research becomes material for studying Indonesian filmmakers in producing films in order to present culture in a more viscous manner, besides that it is also a form of criticism of Batak culture which adheres to the ideology of patriarchal culture.